Phylogenomics, male internal genitalia, a new species, and other notes on New World Stenopelmatus Jerusalem crickets (Orthoptera: Stenopelmatoidea: Stenopelmatini) - Weissman, David B.; Song, Hojun; Vandergast, Amy G. (Zootaxa, 2024)
Based on past and expanded DNA sampling, the orthopteran families Stenopelmatidae and Anostostomatidae, as currently structured, are shown to be non-monophyletic. The splay-footed cricket genus Comicus is confirmed to be genetically distinct from all Stenopelmatidae. We add two specimens to our previously published phylogenetic tree for New World Stenopelmatus Jerusalem cricket species and report the first multilocus DNA recovery for S. ater from Costa Rica. Male internal genitalia may be of systematic value in Jerusalem crickets, but we believe they should be analyzed when in their unfolded, “physiologically functional” configuration, where morphological characters can be seen in more detail when compared to their preserved, folded state. We describe Stenopelmatus nuevoguatemalae n. sp. from Guatemala.